2019
DOI: 10.1109/access.2019.2922358
|View full text |Cite
|
Sign up to set email alerts
|

Solar Array Fed Synchronous Reluctance Motor Driven Water Pump: An Improved Performance Under Partial Shading Conditions

Abstract: An improved performance of a photovoltaic (PV) pumping system employing a synchronous reluctance motor (SynRM) under partial shading conditions is proposed. The system does not include the dc-dc converter that is predominantly being utilized for maximizing the output power of the PV array. In addition, storage batteries are also not contained. A conventional inverter connected directly to the PV array is used to drive the SynRM. Further, a control strategy is proposed to drive the inverter so that the maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…The authors proposed the use of zetta controller to extract maximum power from the solar array that is feeding the BLDC motor-driven water pumping system. Authors in [14] demonstrated a PV-driven synchronous motor water pump with improved control methodology for shading situation. They focused on controller development for optimum power extraction of the PV pannel.…”
Section: Frequently Used Symbols R Smentioning
confidence: 99%
“…The authors proposed the use of zetta controller to extract maximum power from the solar array that is feeding the BLDC motor-driven water pumping system. Authors in [14] demonstrated a PV-driven synchronous motor water pump with improved control methodology for shading situation. They focused on controller development for optimum power extraction of the PV pannel.…”
Section: Frequently Used Symbols R Smentioning
confidence: 99%
“…In this circuit, five electrical parameters are required to simulate the performance of the machine. The five parameters are the stator and rotor resistances (R s and R r ), stator and rotor leakage inductances (L ls , L lr ) and magnetizing inductance (L m ) [17][18][19][20][21][22][23].…”
Section: Im Parameter Determination Based On Pso Algorithmmentioning
confidence: 99%
“…GA is also used in References [14][15][16][17] for determining the parameters of IM based on the manufacturer's published data. The Particle Swarm Optimization (PSO) algorithm is employed to determine the parameters of inductions motors in several publications, for example, References [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…58 PV pumping systems using SynRMs were discussed in a few studies. 57,59,60 However, all these publications use the conventional PV array modules of low efficiency and large installation area.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, synchronous reluctance motors (SynRMs) have a rugged construction, cost‐effective and higher efficiency than that of IMs 58 . PV pumping systems using SynRMs were discussed in a few studies 57,59,60 . However, all these publications use the conventional PV array modules of low efficiency and large installation area.…”
Section: Introductionmentioning
confidence: 99%